The Variation in Levels of Some Male Pituitary and Gonadal Hormones in Beta-Thalassemia Major Patients in Iraq - Yenzeel, Jabaar H. (Iraqi Journal of Science, 2022)
This study was aimed to investigate the iron overload effect on the levels of ferritin, testosterone, follicle stimulating hormone (FSH), luteinizing hormone (LH) and prolactin (PRL) in male patients with β-thalassemia. Blood levels of sex hormones and ferritin were determined in (50 males) beta-thalassemia patients, aged (16-23) years and in (30) healthy males matched for age. They were recruited from the Abin Al-Balady Hospital in Baghdad. Ichroma™ kits were used to determine the blood levels of sex hormones and ferritin. The results showed that the level of testosterone, LH and FSH were significantly (p≤ 0.05) lower in β-thalassemia male patients compared to controls. Furthermore, the level of ferritin and prolactin in male patients were significantly (p≤ 0.05) higher than the values obtained in the controls. Significant positive correlations (p≤ 0.05), (r= 0.3834) were detected between level of LH and ferritin in male patients. Non-significant positive correlations (p≥0.05) in the level of testosterone and ferritin, also non-significant negative correlation in PRL and FSH and ferritin were found in patients with β-thalassemia. From the above results it can be concluded that the iron overload may be the major cause of infertility in β-thalassemia male patients.